Clinical Profile of Birth Asphyxia in Dhulikhel Hospital: A Retrospective Study - Dongol, S; Singh, J; Shrestha, S; Shakya, A (Journal of Nepal Paediatric Society, 2010)
Introduction: Birth asphyxia is defined by the World Health Organization "the failure to initiate and sustain breathing at birth." The WHO has estimated that 4 million babies die during the neonatal period every year and 99% of these deaths occur in low-income and middle income countries. Three major causes account for over three quarters of these deaths, serious infection (28%) complication of preterm birth (26%) and birth asphyxia (23%). This estimation implies that birth asphyxia is the cause of around one million neonatal deaths each year. One of the present challenges is the lack of a gold standard for accurately defining birth asphyxia. Because of same reason the incidence of birth asphyxia is difficult to quantify. Objective: The aim of this study was to assess the prevalence of birth asphyxia, identify the common obstetric and neonatal risk factors, and study the cause of death. Methodology: All babies born in Dhulikhel Hospital (DH) from Jan 2007 to Oct 2009 with a diagnosis of birth asphyxia (5 min Apgar < 7 and those with no spontaneous respirations after birth) were included in the study (n=102). Clinical information was collected retrospectively from maternal records (maternal age, gravida, type of delivery, presence of meconium, induced or spontaneous labour, and pregnancy complications). The NICU records provided additional information about new born infant (birth asphyxia, stages of birth asphyxia, birth weight, sex and subsequent mortality). Results: Among the 3784 live births there were 102 babies with birth asphyxia prevalence of 26.9/1000 live births. Babies with Hypoxic ischemic encephalopathy (HIE) Stage 1 had a very good outcome but HIE III was associated with a poor outcome. Males, primipara and pregnancies with complications were associated with a higher rate of birth asphyxia. Septicaemia, necrotizing enterocolitis, preterm delivery, convulsion and, pneumothorax were associated with higher mortality and morbidity. Conclusion: Birth asphyxia was one of the commonest causes of admission and mortality in NICU. Babies with HIE Stage III had a very poor prognosis. Birth asphyxia combined with other morbidities was associated with a higher mortality. Sepsis is the commonest morbidity in cases of birth asphyxia. Maternal gravida, pregnancy complication with PROM, meconium, APH, emergency caesarean section, preterm and male sex were the risk factors for birth asphyxia. Key words: Birth asphyxia; HIE; Neonatal sepsis DOI: 10.3126/jnps.v30i3.3916 J Nep Paedtr Soc 2010;30(3):141-146